World-Time, Life-Time, and the Time of Architecture - Karsten Harries (Oz, 1998)
1. This year's issue of Oz "seeks to investigate the lasting qualities of architecture within our increasingly intangible society;" you summarize your "interests in this topic in a simple question with dual meaning: what gives a building substance in time"?